1. A(x)= 3x^2 + 6x - 5; B(x)= x-3 . Determinar A(x) - B(x)
2. 2zy + 4y + 5z ; para y= 3, z = 2
3. 5^2 ÷ 5 +9 - 3 x 2^3 -330+ 12-25=
4. P(x) = 3x^4 - 4
5. m x - 2m x+5 ; para m = 2, x = 1
6. 5 x^2 + 4ab - 4x^2 + 3ab - 5c
7. P(x) = 7 + x^4 - x + 5x^2 - 6x + 3x^3 - 4
8. Simplificar: [π / 5^7 ]^0
ayúdenme son para un examen
Respuestas a la pregunta
Contestado por
0
1 -57 2 34 3 -332 las demas noc
Otras preguntas
Contabilidad,
hace 2 meses
Inglés,
hace 2 meses
Ciencias Sociales,
hace 5 meses
Matemáticas,
hace 10 meses